Design and flight analysis of the Kenyalang-1 fuel cell powered unmanned aircraft / Thomas A. Ward - Ward, Thomas A. (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2012)
The Kenyalang-12 is an unmanned technology demonstrator aircraft equipped with a hydrogen fuel cell to provide power for its electric propulsion system. This aircraft was designed, built, and flight-tested at the Universiti Teknologi MARA Flight Technology and Test Center located in Shah Alam, Malaysia. It is the first of its kind entirely designed, built, and test flown in Southeast Asia. The fuel cell is capable of providing 500 W of continuous power, fed by hydrogen gas that is stored in a pressurized tank. The only exhaust product of this power system is water vapor, making it environmentally clean. Since fuel cells are solid state devices that generate power using electrochemical (noncombustion) processes, the power system is mechanically reliable, quiet, and generates much less heat than conventional combustion engines. Two types of power systems were flight-tested: Type A (consisting only of the fuel cell) and Type B (a pseudo-hybrid design that added a two-cell lithium polymer battery in series to augment the fuel cell). Flight telemetry of the aircraft configured with each of the two power systems provides a design and performance baseline for a future generation of fuel cell powered aircraft.